The effect of sensitization and fatigue loading frequency on corrosion fatigue of AA5083-H131. (July 2019) - Bay, Rebecca M.; Schrock, David J.; Akman, Allison M.; Bland, Leslie G.; Thodla, Ramgopal; (Warner) Locke, Jenifer S.
Highlights: Microstructures with low DoS exhibit f -independent corrosion fatigue kinetics. High DoS microstructures increase CF da/dN 10× for every 10× decrease in f. CF da/dN of high DoS microstructure is 1000× higher than AR material at 0.01 Hz. Abstract: Corrosion fatigue crack growth rates (da/dN) of AA5083-H131 when loaded in 3.5 wt% NaCl increase as the level of sensitization increases and exhibit a strong inverse fatigue loading frequency dependence when heavily sensitized. High Mg 5xxx series Al alloys are known to exhibit decreased resistance to intergranular corrosion and intergranular stress corrosion cracking due to the formation of the active Al3 Mg2 -β phase on grain boundaries when exposed to slightly elevated temperatures for prolonged periods of time, a phenomenon known as sensitization. High resolution fracture mechanics based experiments conducted at constant ΔK and R-ratio under full immersion in 3.5 wt% NaCl show that da/dN in a heavily sensitized microstructure increases by an order of magnitude for each order of magnitude decrease in fatigue loading frequency, while da/dN for the as-received and unsensitized microstructure has little to no frequency dependence. Futhermore, for higher frequency loading at 1 Hz, da/dN for the highly sensitized microstructures is one order of magnitude higher than the as-received microstructure; while for the low frequency loading at 0.01 Hz, da/dN for the highly sensitized microstructure is three orders of magnitude higher than the as-received microstructure. The findings of this study suggest that typical higher frequency laboratory testing studies at 10 Hz may severely underestimate fatigue life under service relevant loading conditions.